2015
DOI: 10.1097/gco.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

A link between human papilloma virus vaccination and primary ovarian insufficiency

Abstract: The mechanisms responsible for POI are not yet fully understood. Although case reports cannot establish causation, awareness of a possible link between HPV4 and POI will help to identify and manage future cases that may arise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…Similarly, other investigators observed a case series of three women that had onset or exacerbation of lupus following HPV immunization [12]. Other researchers have suggested that an increasing number of cases of ovarian damage has been observed following HPV4 vaccine administration [13]. …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, other investigators observed a case series of three women that had onset or exacerbation of lupus following HPV immunization [12]. Other researchers have suggested that an increasing number of cases of ovarian damage has been observed following HPV4 vaccine administration [13]. …”
Section: Discussionmentioning
confidence: 83%
“…Other investigators described animal models that showed aluminum exposure to inhibit expression of female reproductive hormones and to induce histologic changes in the ovaries [13]. …”
Section: Discussionmentioning
confidence: 99%
“…The possible trigger for this has been reported to be aluminium‐containing adjuvant in the vaccine preparation, which increases the immune reaction, termed as autoimmune/inflammatory syndrome induced by adjuvants (ASIA) . Furthermore, the idea of autoimmunity in this case was supported by the presence of anti‐ovarian and anti‐thyroid peroxidise Abs …”
Section: Molecular Mimicry: the Conceptmentioning
confidence: 88%
“…The health registry-based surveillance was more sensitive than the conventional SAE surveillance. This kind of health registry-based quantitative analysis is an important adjunct to the safety data on the HPV-16/18 vaccine and will in the future continue to be most appealing to health authorities in the context of newly licensed vaccines for suspected or alleged vaccine-associated adverse effects (e.g., autism, narcolepsy) or in the case of HPV vaccination, primary ovarian failure syndrome 29 or miscarriage 23,30-32 …”
Section: Discussionmentioning
confidence: 99%